Experts and epistemic monopolies - Koppl, Roger, 1957-; Horwitz, Steven; Dobuzinskis, Laurent (Advances in Austrian economics ;, 2012)
In almost every corner of our private and public lives we rely on experts to advise us. This important species of labor is getting increasing attention from economists, who are beginning to learn how to apply their tools and assumptions to the problem of expertise. Under what conditions of supply and demand are experts likely to give us good advice? When is expert failure more likely? Do entrepreneurs challenge existing expertise? Are they experts themselves? And if economists are themselves experts, what happens when we turn the skeptical gaze of economic theory on the economist themselves? This volume publishes papers given at the third biennial Wirth Institute Conference on Austrian Economics. It brings together a heterogeneous collection of thinkers, some "Austrian" and others not, to critically engage the problem of experts. While mostly agreeing that there is a problem of experts, the papers collected here approach the issue from a variety of often-complementary perspectives.